The Relationship between Knowledge, Attitudes, and Behaviors Toward Genital Health - Ike Martyani; Imam Budi Putra (GLOBAL HEALTH SCIENCE GROUP, 2026)
Genital health is a fundamental component of reproductive health and significantly influences physical, psychological, and social well-being. However, the relationship between knowledge, attitudes, and behaviors toward genital health remains underexplored, particularly among male populations. The aim of the study was to examine the simultaneous relationship of knowledge and attitudes with behaviors in maintaining genital health among male. This cross-sectional analytical study involved 608 male respondents selected through purposive sampling. Data were collected using a structured questionnaire assessing knowledge, attitudes, and behaviors related to genital health. Descriptive statistics were used to summarize respondent characteristics, and associations between variables were analyzed using the Chi-square test with a significance level of p < 0.05. Most respondents demonstrated good knowledge (73.8%) and positive attitudes (88.8%) toward genital health. However, behavioral practice was divided between moderate (51.3%) and good (48.5%) categories. A significant association was observed between knowledge and behavior (p = 0.007) and between attitude and behavior (p = 0.001), indicating that higher knowledge and more positive attitudes were strongly associated with better genital health practices. Knowledge and attitudes are key determinants of genital health behavior. Interventions aimed at improving male genital health should integrate educational strategies that enhance knowledge while simultaneously fostering positive attitudes to achieve sustainable behavioral change.